Dynamic frontal crash performance of old and used child restraint systems. (3rd October 2021) - Whyte, Tom; Kent, Nicholas; Griffiths, Michael; Bilston, Lynne E.; Brown, Julie
Abstract: Objective: To examine the effect of age on the dynamic performance of child restraint systems in frontal crashes. Methods: A sample of used (3-269 months from manufacture) and newly purchased child restraints were subjected to frontal crash simulations of more than 56 km/h and peak deceleration approximately 33 g on a deceleration sled. Restraints were monitored for evidence of damage before and after each impact. Anthropometric test device (ATD) head and chest responses and peak head excursions were recorded for rearward facing restraints using the Q1 ATD and for forward facing restraints and booster seats using the Q6 ATD. The influence of restraint age on peak 3 ms head acceleration, HIC15, head excursion, peak 3 ms chest acceleration and restraint damage were analyzed. Results: In all impacts, the ATD remained within the restraint and secured to the test bench demonstrating the crash protection offered by the old and used restraints. There was no apparent relationship between ATD responses and restraint age for any restraint type. Older forward facing restraint systems had a very modest increase in forward head excursion (R 2 = 0.59, p = 0.001) of 0.27 mm for each month of age (95% CI, 0.13 mm − 0.42 mm). This equates to a 0.7% increase in the minimum measured excursion per year of restraint age. There was also a small increased likelihood of critical damage to the restraints in the simulated crashes per month of restraint age (OR 1.031, 95% CI 1.010-1.069). Conclusions: Overall, degradation in restraint dynamic performance in older restraints, including some that are much older than the currently recommended 10-year lifetime, is minimal. However newer restraints may provide better protection due to marginal improvements in restraint design over time. Furthermore, the results of this study confirm previous recommendations that restraints should not be re-used after crash involvement.